2019
DOI: 10.1016/j.wear.2019.203049
|View full text |Cite
|
Sign up to set email alerts
|

Crack formation within a Hadfield manganese steel crossing nose

Abstract: Switches and crossings in rail networks suffer from complex loading which may induce severe damage and defects, including formation of cracks that can result in rail breakage. This paper focuses on the microstructure and crack network in a damaged Hadfield manganese steel crossing nose. The extent of deformation has been quantified by hardness measurements, optical microscopy and scanning electron microscopy (SEM) including electron back scattering diffraction (EBSD). It is found that the wheel contact causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…Figure 7 shows an optical micrograph of a subsurface crack in the wing rail of the manganese steel crossing investigated in this work having the same wavy appearance intersecting several grains with several crack branches and a seemingly random crack propagation. This is in correspondence to the cracks found in a manganese steel crossing nose studied previously in [9], where a more detailed study showed the cracks avoided the twinned regions (harder areas of the matrix) and were mostly transgranular giving the wavy appearance by following the weakest link in the microstructure. Therefore, although the plastic deformation is caused by slip in pearlitic grade without twinning, and for manganese steel deformation is from both dislocation motion as well as twinning, the crack networks have a similar appearance for pearlitic steel straight tracks and manganese steel crossings irrespective of the very different loading conditions in the two cases.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Figure 7 shows an optical micrograph of a subsurface crack in the wing rail of the manganese steel crossing investigated in this work having the same wavy appearance intersecting several grains with several crack branches and a seemingly random crack propagation. This is in correspondence to the cracks found in a manganese steel crossing nose studied previously in [9], where a more detailed study showed the cracks avoided the twinned regions (harder areas of the matrix) and were mostly transgranular giving the wavy appearance by following the weakest link in the microstructure. Therefore, although the plastic deformation is caused by slip in pearlitic grade without twinning, and for manganese steel deformation is from both dislocation motion as well as twinning, the crack networks have a similar appearance for pearlitic steel straight tracks and manganese steel crossings irrespective of the very different loading conditions in the two cases.…”
Section: Discussionsupporting
confidence: 90%
“…The work hardened layer is observed to extend to 10 mm below the surface. This depth of the deformation in the investigated wing rails is found to be nearly the same as found in case of the manganese nose rail studied previously [9]. Although the previously studied crossing was fairly a new one (5 years in service) compared to the crossing in the present study (13 years in service), the yearly traffic density through both the switches was approximately the same (14MGT).…”
Section: Hardnesssupporting
confidence: 86%
See 3 more Smart Citations